Bilateral Thyroid Carcinosarcoma in a Cat. (August 2019) - Rich, A.F.; Piviani, M.; Swales, H.; Finotello, R.; Blundell, R.
Summary: A neutered female domestic shorthaired cat was presented for a rapidly growing left cervical mass and a 6-month history of primary hyperthyroidism. Cytological examination of the mass was consistent with a sarcoma. Due to poor clinical response the cat was humanely destroyed and a post-mortem examination was performed. This revealed a markedly enlarged, irregularly shaped left thyroid gland with signs of infiltration of the trachea. The contralateral (right) thyroid was also moderately enlarged and irregularly shaped. Histopathological examination of the cervical masses indicated bilateral thyroid carcinosarcomas, evidenced by positive immunohistochemical labelling for vimentin, pan-cytokeratin and thyroid transcription factor-1 of the appropriate cell populations. The cat also had a concurrent pulmonary adenocarcinoma (papillary-lepidic type), unrelated to the thyroid neoplasm. Thyroid carcinosarcoma is an uncommonly recorded canine and human neoplasm and this is the first case of this entity to be reported in a cat.